Analysis of Factors That Affecting on Use E-Bupot 23/26 - Andi Muhammad Dahlan (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2022)
The e-Bupot 23/26 application is used to make evidence of withholding and reporting Income Tax Article 23/26. There are many factors that affect the use of the application. This study aims to examine and analyze the effect of perceived usefulness, ease of use, and behavior control on the use of e-Bupot 23/26 at the North Makassar Pratama Tax Service Office. This study uses a quantitative approach through a questionnaire. There are 50 samples analyzed with multiple linear analysis model. The results showed that perceived usefulness had a positive and significant effect on the use of e-Bupot 23/26. However, perceived ease of use and perceived behavior control have no effect on the use of e-Bupot 23/26 due to the use of the application, which is still only for most taxpayers.